Price volatility of strategic commodities : correlation or causation. - Koh, Deng Qiang. (2013)
Commodity prices have been observed to experience sharp fluctuations. Oil prices have spiked to US$146 per barrel in August 2008 but subsequently plunged to less than a quarter of this value in December 2008. Agricultural commodities are not spared either with the food price crisis of 2007-08 and followed by another large spike in 2011. It is becoming increasingly evident that an economy faces higher and more volatile commodity prices. The conventional wisdom is that crude oil prices are more volatile than other commodities ever since the oil crisis in 1973. However, the question whether crude oil prices are really more volatile than other commodity prices is a complicated question. This study examines three questions. First, if crude oil prices are always more volatile since the collapse of commodity prices in 1986. Second, do price shocks have asymmetric effects on volatility? Third, is there correlation, cointegration or even causality between the movements of commodity prices? Brent is set as a benchmark against two other sub categories of commodities, precious metals (gold and silver) and agricultural commodities (wheat, corn and soybean). The period of testing is from January 1986 to Dec 2012. It is expected that all commodities’ returns plots demonstrate volatility clustering in which a large volatility change is followed by large volatility and a small volatility change is followed by small volatility.